The Suppression of miR-199a-3p by Promoter Methylation Contributes to Papillary Thyroid Carcinoma Aggressiveness by Targeting RAP2a and DNMT3a - Wu, Feng; Lin, Xiao; Shan, Su-Kang; Li, Fuxingzi; Xu, Feng; Zhong, Jia-Yu; Guo, Bei; Zheng, Ming-Hui; Wang, Yi; Mo, Zhao-Hui; Yuan, Ling-Qing (Frontiers in Cell and Developmental Biology, 2020)
Background: It was previously demonstrated that miR-199a-3p plays an important role in tumour progression; especially, its down-regulation in papillary thyroid cancer (PTC) is associated with cancer cell invasion and proliferation. In the present report, we investigated the mechanism involved in the down-regulation of miR-199a-3p in PTC and how miR-199a-3p regulates PTC invasion both in vivo and in vitro. Methods: qRT-PCR and Western blot assays were used to determine the expression of the investigated genes. Bisulphite sequencing PCR was used to investigate miR-199a-3p methylation. The functions of miR-199a-3p were investigated by a series of in vitro and in vivo experiments. Results: Our results showed hypermethylation of the miR-199a-3p promoter, which resulted in decreased miR-199a-3p expression both in PTC cell lines and PTC tissues. DNA-methyltransferase 3a (DNMT3a), a target gene of miR-199a-3p, was increased both in PTC cell lines and PTC tissues, while 5-aza-2'-deoxycytidine (methyltransferase-specific inhibitor) or knock-down using DNMT3a siRNA could restore the expression of miR-199a-3p, and the over-expression of miR-199a-3p could decrease the expression of DNMT3a; this suggests that miR-199a-3p/DNMT3a constructs a regulatory circuit in regulating miR-199a-3p/DNMT3a expression. Moreover, gain- and loss-of-function studies revealed that miR-199a-3p is involved in cancer cell migration, invasion and growth. Meanwhile, we found that RAP2a was also a direct target of miR-199a-3p, which might mediate the tumour-growth-inhibiting effect of miR-199a-3p. To further confirm the tumour-suppressive properties of miR-199a-3p, stable overexpression of miR-199a-3p in a PTC cell line (BCPAP cells) was xenografted to athymic BALB/c nude mice, resulting in delayed tumour growth in vivo. In clinical PTC samples, the expression of RAP2a and DNMT3a was increased significantly, and the expression of RAP2a was inversely correlated with that of miR-199a-3p. Conclusions: Our studies demonstrate that an epigenetic change in the promoter region of miR-199a contributes to the aggressive behaviour of PTC via the miR-199a-3p/DNMT3a regulatory circuit and directly targets RAP2a.